Effects of high-fat diet-induced obesity and diabetes on Kiss1 and GPR54 expression in the hypothalamic–pituitary–gonadal (HPG) axis and peripheral organs (fat, pancreas and liver) in male rats. (April 2016) - Dudek, M.; Kołodziejski, P.A.; Pruszyńska-Oszmałek, E.; Sassek, M.; Ziarniak, K.; Nowak, K.W.; Sliwowska, J.H.
Abstract: Recent data indicates that kisspeptin, encoded by the KISS1 gene, could play a role in transducing metabolic information into the hypothalamic–pituitary–gonadal (HPG) axis, the mechanism that controls reproductive functions. Numerous studies have shown that in a state of negative energy balance, the hypothalamic kisspeptin system is impaired. However, data concerning positive energy balance (e.g. diabetes and obesity) and the role of kisspeptin in the peripheral tissues is scant. We hypothesized that: 1) in diet-induced obese (DIO) male rats and/or rats with diabetes type 1 (DM1) and type 2 (DM2), altered reproductive functions are related to an imbalance in Kiss1 and GPR54 mRNA in the HPG axis; and 2) in DIO and/or DM1 and/or DM2 rats, Kiss1 and GPR 54 expression are altered in the peripheral tissues involved in metabolic functions (fat, pancreas and liver). Animals were fed a high-fat or control diets and STZ (streptozotocin — toxin, which destroys the pancreas) was injected in high or low doses to induce diabetes type 1 (DM1) or diabetes type 2 (DM2), respectively. RT-PCR and Western blot techniques were used to assess the expression of Kiss1 and GRP54 in tissues. At the level of mRNA, we found that diabetic but not obese rats have alterations in Kiss1 and/or GPR54 mRNA levels in the HPG axis as well as in peripheral tissues involved in metabolic functions (fat, pancreas and liver). The most severe changes were seen in DM1 rats. However, in the case of protein levels in the peripheral tissues (fat, pancreas and liver), changes in Kiss1/GPR54 expression were noticed in DIO, DM1 and DM2 animals and were tissue-specific. Our data support the hypothesis that alterations in Kiss1/GPR54 balance may account for both reproductive and metabolic abnormalities reported in obese and diabetic rats. Highlights: Kiss1/GPR54 is expressed in the HPG axis and peripheral tissues involved in metabolic functions (fat, pancreas and liver). Diabetic but not obese rats have alterations in Kiss1 and/or GPR54 mRNA levels in the HPG axis as well as in peripheral tissues. In the case of protein, changes in Kiss1/GPR54 expression were noticed in DIO, DM1 and DM2 animals and were tissue-specific. Alterations in Kiss1/GPR54 expression may account for reproductive and metabolic abnormalities in obese and diabetic animals.